Penggunaan KB Pada Wanita Usia Subur - Ningrum, Yuriana Cahya; Putri, Riska Hediya; Yunitasari, Eva (Wellness And Healthy Magazine, 2021)
Women of childbearing age are women who enter the age between 15-49 years without taking into account their marital status. Women of childbearing age have reproductive organs that are still functioning properly, making it easier to get a pregnancy, which is between the ages of 20 to 45 years. Injectable contraception has advantages and disadvantages. Lack of injection contraception is disrupted menstruation patterns among which are amenorrhea, menorrhagia, and spots that appear, delay in returning fertility after cessation of use, weight gain. Indonesian and English that meet the PICO and SPIDERcriteria Because of the limitations of the article, quantitative studies are used to get a more accurate review. Based on the analysis of the journal there are nursing implications that have been compared from the 10 journal opinions of researchers of many women of childbearing age who diligently exercise and eat healthy foods to maintain a healthy diet to prevent weight gain in women of childbearing age who use KB injections.